Fluorescent‐conjugated antibodies as rapid ex vivo markers for bacterial presence on orthopedic surgical explants and synovium: A pilot study. Issue 2 (2nd December 2020) - Garcia, Dioscaris; Gardezi, Mursal; Suliman, Yasmine; Glasser, Jillian; Spake, Carole SL; Barrett, Caitlin; Berns, Ellis; Jenkins, Derek; Evans, Andrew; Cohen, Eric; Eberson, Craig; Hayda, Roman; et al.
Abstract: Surgical infection is one of the most pressing problems in the field of orthopedic surgery; however, current detection methods are plagued by high costs and long wait times. This study seeks to demonstrate the ability of a novel assay using fluorescently conjugated antibodies and confocal laser scanning microscopy (CLSM) to accurately detect bacterial presence on orthopedic surgical explants, tissue, and synovial fluid in 30 min. Explanted hardware, tissue, and synovial fluid samples suspected to be infected were collected from human subjects with institutional review board consent. Samples were prepared using a 30‐min protocol, consisting of rinsing, nonspecific blocking and staining steps, and imaged using CLSM. Images were analyzed using ImageJ (National Institute of Health) to determine the percent area of Gram positive and Gram negative bacteria. Results of the assay were compared to the hospital's microbiological laboratory and Gram staining results. Ninety three samples were collected and tested using the 30‐min testing protocol; 75 samples were synovial fluid and 18 were tissue and explants. Seventy four of 75 (98.6%) synovial fluid samples correlated with the hospital laboratory's microbiological findings. Of the 18 explant and tissue samples, our assay found bacterial presence in 14 of 18 samples, while the hospital microbiology laboratory found bacterial presence in 13 of 18 samples. This assay reliably stained and rapidly identified the presence of Gram negative and Gram positive bacteria on surgical explants, tissue and synovial fluid in 30 min. This methodology may serve as a point of service tool for the determination of bacterial presence during surgical procedures.